Study on chloroquine containing ability of minicells derived from Lactobacillus acidophilus ATCC 4356 - Tu My Ho, Yen Thi Hai Tran, Tu Hoang Khue Nguyen (Journal of Applied Pharmaceutical Science, 2024)
Site-specific nano-drug delivery systems have been researched and have become a new strategy to change the use and reduce the toxicity of chemical drugs. One potential carrier is the minicell from lactic acid bacteria. It is one of the potential carriers since it can be modified with specific antibodies, packaged with a high drug concentration, and is a safe source for humans. In this study, Lactobacillus acidophilus (L. acidophilus) ATCC 4356 minicells were generated by using sugar stress and tested the chloroquine (CQ) containing ability. Lactobacillus acidophilus ATCC 4356 formed a high concentration of 107 minicells/ml after 20–24 hours of culturing in modified broth containing 1% D-fructose. Lactobacillus acidophilus ATCC 4356 minicells were incubated with CQ at different periods (1, 2, 3, and 4 hours) at 37°C. The presence of CQ was detected by high-performance liquid chromatography. The result indicated that minicells could contain a huge amount of the drug (1.34 mg/ml) after 1 hour. Moreover, the releasing test was performed at two conditions (pH 3 and pH 7). After 0.5 hours, a modest concentration of the drug was observed to be leaking, which maximized after 2 hours. In addition, this study also proved the binding of CQ onto the minicells’ cell wall by using the Fourier transform infrared spectroscopy technique and molecular docking for predicting interaction. This study contributed to new drug innovations in the pharmaceutical field.
Keywords: Nano-sized minicells, chloroquine, drug delivery system, high-performance liquid chromatography, Fourier transform infrared spectroscopy, molecular docking